Evaluation of Optimum Insulation Thickness According to External Wall Types to Be Used in Buildings to Be Reconstructed in Turkey - Cisil Timuralp; Nil Aras; Nuri Sisman; Haydar Aras (Applied Sciences)
The external walls of a building represent the interface between the interior and exterior environments. Insulating external walls represents the most cost-effective means of ensuring indoor comfort. Despite the prevailing assumption that insulation will increase the cost of the building, this study has demonstrated that this is not the case. Notwithstanding the increase in investment costs, the application of insulation to the external walls has been demonstrated to result in a reduction in fuel consumption and operating costs. In accordance with TS 825, there are five distinct degree-day zones, with the requisite heat loads in these zones exhibiting variability. Accordingly, a cost-based methodology is required to ascertain the optimal insulation thicknesses for the various degree-day zones. In this study, the gains to be obtained in the case of using three different insulation materials for five different wall types to be used in the buildings to be built instead of the buildings destroyed in the earthquake in Turkey in 2023 were analyzed. Samples from three degree-day zones affected by earthquakes were assessed for insulation, wall structures, and fuel types. The study assesses optimum insulation thickness, investment cost, annual fuel savings, annual economic benefits, and investment payback period.